WAKAF SEBAGAI DASAR MENINGKATKAN KESEJAHTERAAN DAN SUMBER DAYA MANUSIA: (Studi Penerapan Wakaf Produktif dan Tunai Di Aceh) - Mukhlisuddin, Teuku (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
Before the Indonesian nation proclaimed its independence, the Indonesian people had often made waqf. This waqf practice is in line with the many Islamic kingdoms in Indonesia, such as the Demak kingdom, the Pasai kingdom, the Mataram kingdom and so on. The implementation of waqf that develops in society is carried out based on Islamic teachings that originate from Islamic values. Looking at waqf historically, it has actually taught Muslims the importance of continuous economic resources to ensure ongoing prosperity in society. Waqf as an economic instrument that gives life to its managers and the community. Waqf is an important socio-economic pattern of worship. Waqf is to build the economy and civilization. Waqf has an economic basis. Therefore, we must make waqf the backbone of sharia economic development. In building an Islamic economy, waqf cannot stand alone, but is a package with zakat, infaq and alms. The author sees the concept of cash waqf in Aceh as having tremendous potential to support the economic development of the people, because the funds are also available from sources of zakat, infaq, endowments, and other religious assets. These sources of funds are managed in an integrated manner at Baitul Mal Aceh. The management of zakat and waqf is not separate as at the national level. According to classical Islamic history, waqf has played a very significant role in improving the welfare of Muslims, both in the fields of education, health services, social services and public interests, religious activities, development of science and Islamic civilization in general. Waqf as an economic instrument that gives life to its managers and the community. Not the other way around, waqf only becomes a burden on managers and demands a helping hand of generosity from the community. Waqf during the friendship era has become an economic source and financing for the development of science, such as during the Caliphate era of Harun al Rasyid with the Bayt al Hikmah library which was financed by waqf wealth.